The Efficiency of The Spot Market And Crude Palm Oil (CPO) Commodity Futures Market Before and During The Covid-19 Pandemic in Indonesia - Gandhy, Abel; Harianto; Nurmalina, Rita; Suharno (Jurnal Manajemen & Agribisnis, 2022)
CPO prices fluctuation cause price uncertainty formed in the future. Hedging is an activity carried out by market participants to mitigate the risk of price fluctuations. The Covid-19 pandemic disrupts the supply and demand of CPO, affecting price alteration, especially in the spot and futures markets. This study determines market efficiency and the CPO price asymmetry relationship between the Medan spot market, the Jakarta futures market, the Malaysian futures market, and the Rotterdam forward market prior to and during the COVID-19 pandemic. The data used in this study are daily price data on each market from January 2016 to December 2020. They are analyzed using the NARDL model. There is a price asymmetry relationship between the spot and futures markets preceding and during the covid-19 pandemic. The increase in CPO prices causes a more significant impact than the decline in prices in the long term. In addition, there is also a long-term and short-term efficient relationship between the spot market and the futures market for CPO commodities. Thus, the hedging function performed by the CPO commodity market participants will run effectively. Keywords: CPO Price, NARDL Model, Market Efficiency, Cointegration, Pandemic Covid-19